Dynamic beam shut-off algorithm for LEO satellite constellation - Shuaijun LIU; Yuemei HU; Chunshi FAN; Teng LING; Lixiang LIU (Tongxin xuebao)
Aiming at the problems of the relatively dense coverage of the satellites in the space segment of the low earth orbit (LEO) multibeam satellite constellation network,which resulted in relatively dense areas in some regions,causing severe inter-beam interference and unnecessary beam resource overhead,a beam shut-off algorithm was proposed with global coverage requirements.The dynamic beam shut-off (DBSO) optimization problem was formulated in LEO multibeam satellite constellation network.Then,the problem was proved to be NP-complete and a heuristic DBSO algorithm was proposed.Simulation scenario considers the Iridium constellation network scenario with total 3 168 beams,and it shows that the number of required activated beams is only 1 913 with 39.61% beam resource reduction.